Comparative study of intrathecal bupivacaine in combination with nalbuphine and bupivacaine for subarachnoid block in a tertiary care hospital - Lavanya Bachula; Nallolla Rahul Dev; P.V. Shiva; Sunil Kumar Cherukuri (Journal of Research in Clinical Medicine)
Introduction: Various adjuvant therapies have been developed to prolong intra and postoperative analgesia. A comparative study was conducted to evaluate the onset, maximum level, and duration of motor and sensory block, as well as the duration of analgesia, side effects like hypotension, bradycardia, sedation, and respiratory depression in patients undergoing elective lower segment caesarean section (LSCS). Methods: The study included 60 patients, divided in to two groups to receive intrathecal hyperbaric bupivacaine (0.5%) in combination with nalbuphine (0.8 mg) (group A) and intrathecal hyperbaric bupivacaine alone (group B). Demographic data, onset of sensory and motor block, regression of motor block, duration of analgesia, hemodynamic changes, and side effects during the procedure were recorded. Results: A statistically significant difference was observed in time of onset of sensory and motor block, and maximum percentage of sensory block was attained in group B (bupivacaine) with 90% of patients. Mean duration of sensory regression to S1 was attained at 120.16 minutes in group A (bupivacaine+nalbuphine). Mean duration of analgesia was attained at 203.33 minutes in group A, and haemodynamic parameters have remained below the baseline value in both the groups. Side effects during the surgery were statistically insignificant. Conclusion: Intrathecal nalbuphine (0.8 mg) is an effective adjuvant to 0.5% hyperbaric bupivacaine in subarachnoid block for patients undergoing elective LSCS. It provides prolonged postoperative analgesia without much side effects and may be used as a better alternative over other opioids.